Mind the gap: Congruence between present and future motivational states shapes prospective decisions. (September 2019) - Setton, Roni; Fisher, Geoffrey; Spreng, R. Nathan
Abstract: Poor estimation of one's future actions has been associated with the influence of reward over executive control processes during prospection. However, the neural mechanisms underlying this reward-control trade-off remain poorly understood. In the present study, we take advantage of projection bias, underestimating how motivations will change in the future, to examine brain and behavior changes during prospection about future decisions. To manipulate motivation, we altered satiety (hungry vs. satiated) and asked human participants (N = 25) to place bids on snack foods while undergoing fMRI scanning across two sessions. While hungry, participants bid for the right to consume snacks in both a future congruent motivational state (hungry) and a future incongruent motivational state (satiated). In a second session, while satiated, participants placed bids for the right to immediately consume the items. Imagination of a congruent future state was associated with brain activity in regions implicated in prospection. Imagination of an incongruent future state was related to brain activity in areas related to cognitive control. Projection bias, the difference between bids during incongruent prospection (hungry to satiated, session one) and realization (satiated, session two), was negatively related to thalamic and insular engagement. Bias was positively related to engagement of the ventral striatum, a region involved in reward processing. These results suggest that the relative activation between reward and control systems is influenced by the congruence of present and future motivational states, and shapes bias in predictions about future behavior. Highlights: Individuals miscalculate value of food items in dissimilar future context (bias). Imagination of similar context to the present involves caudate and hippocampus. Imagination of dissimilar context related to regions involved in cognitive control. Bias positively related to brain activity in ventral striatum. Bias negatively related to brain activity in thalamus and posterior insula.